Hope for Eritrea's highlands - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Drought and poverty are devastating combinations for any country and its people, but few countries have also suffered theyears of war that have affected the State of Eritrea. At the end of the Ethio-Eritrean conflict in 1991 the casualties of the...